Legal Certainty for Companies That Unilaterally Terminate Employment Relations to Workers - Aurelius Steven Beale; Rasji (Journal of Law, Politic and Humanities, 2024)
In this study, we have discussed legal certainty for companies in carrying out the process of unilateral termination of employment relations against workers. This study applies a normative juridical research method with the approach taken, namely the legislative and conceptual approaches. This study explains the procedure for legal termination of employment, as well as aspects of legal certainty, especially for companies, and also explains the impacts such as legal and economic impacts of termination disputes. The results of this study prove that there is legal certainty for companies that can be accepted based on compliance with the legal termination procedure, namely by bipartite negotiations, mediation, and fulfillment of legal requirements according to the reasons for termination. The company has the right to validate the reasons for termination of employment and has legal protection in the industrial relations court.